Penerapan PSAK 57 terhadap Kualitas Laporan Keuangan Perusahaan Publik di Indonesia - Inggit Anggraeni; Innaya Ramadhanty; Maya Kusuma Dewi; Nur Ageng Sebayu; Rinny Meidiyustiani (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to assess the effect of PSAK 57 implementation on the quality of financial statements in Indonesian public companies. PSAK 57 is significant because it facilitates the presentation of uncertain liabilities and assets in an honest, relevant, and transparent manner, which ultimately strengthens stakeholder confidence in these financial statements. This study applies a descriptive quantitative approach using secondary data, namely annual reports and financial statements from public companies listed on the Indonesia Stock Exchange (IDX) within a certain period. The evaluation was conducted to measure the degree of compliance with PSAK 57 and its relationship with financial statement quality parameters, such as relevance, reliability, and comparability. The research findings indicate that the implementation of PSAK 57 has a positive impact on the quality of financial statements, as entities that consistently adopt this standard demonstrate higher levels of transparency and accountability. This conclusion conveys a crucial message to practitioners and regulators to continue to deepen their understanding and implementation of PSAK 57 in order to strengthen the quality and integrity of financial reporting in Indonesia.